Do traditional fishers recognise reef fish species declines? Shifting environmental baselines in E astern B razil - M. G. Bender; S. R. Floeter; N. Hanazaki (Fisheries Management and Ecology, 2013)
Local fisher knowledge is an important source of information for the adjustment of environmental baselines relative to anthropogenic impacts on marine ecosystems. This knowledge is also susceptible to the shifting baseline syndrome. Four generations of fishers neighbouring a marine park in Eastern Brazil, were surveyed regarding the conservation status of nine reef fish species. Shifts in environmental baselines were detected among fisher generations. Fishers older than 50 years not only caught larger individual fish, but catches of large fish occurred four decades ago, suggesting that bigger fish are in decline in the region. Of nine reef fish species, seven exhibited significant declining catch trends based on information provided by fishers. Such declining status was not reported by all informants of younger generations, so the ability to identify such species increases significantly with fisher age. The fish species most cited as overexploited were M ycteroperca bonaci (Poey), E pinephelus morio (Valenciennes) and O cyurus chrysurus ( B loch), emphasising that special attention should be given to the management and conservation of these species in E astern B razil. These results also showed that knowledge acquired by elder fishers (> 50 years old) can provide valuable insights into the conservation status of reef fish and the adjustment of environmental baselines for proper management of a marine park.